The Students’ Ability in Using Derivational Suffixes at Persada Bunda School of Foreign Language Pekanbaru - Diana Zuriati (STBA Prayoga Padang, 2019)
The purpose of this research was to know the students’ ability in using derivational suffixes especially about noun. There are three types of derivational suffixes of noun in English, they are: derivational suffixes of nouns derived from nouns, derivational suffixes of nouns derived from verbs and derivational suffixes of nouns derived from adjectives. The method used in this research was quantitative descriptive method. Population of this research was the fifth semester students in academic year 2017/2018 counted 20 people from STIBA Persada Bunda. The instrument used to collect data was a multiple choice test. The results showed that: (1) the ability of the fifth semester students to use the derivational suffix of nouns derived from the noun was 74.5%, (2) use the derivational suffix of nouns derived from verbs was 69%, and (3) use the derivational suffix of nouns derived from adjective was 65%. Briefly it can be concluded that students of semester five academic year 2017/2018 STIBA Persada Bunda Pekanbaru were able to use both the derivational suffix of nouns derived from the noun and the derivational suffix of nouns derived from verbs in good level while the students’ ability in using derivational suffix of nouns derived from adjective was in fair level.